PROXIMATE AND AMINO ACID COMPOSITIONS OF THE POND-CULTURED SPOTTED BARB, PUNTIUS BINOTATUS - Lim, Leong-Seng; Chor, Wei-Kang; bin Firdaus, Rian Freddie; Malitam, Linus; Ransangan, Julian; Shapawi, Rossita (Malaysian Journal of Science, 2015)
The pond culture of spotted barb (Puntius binotatus) has been started in Sabah. However, the nutritional values of these cultured P. binotatus as a protein source for human consumption have never been assessed. Therefore, the proximate and amino acid compositions of these cultured P. binotatus (n = 6, 3 females and 3 males) were evaluated to provide baseline information on its nutritional quality. The fish whole body contained about 18% and 9% of crude protein and lipid, respectively (in wet weight basis), 11% ash and 67% moisture. These proximate values were comparable to the wild-caught P. binotatus as reported in previous study. In addition, the cultured P. binotatus contained high levels of glutamic acid, aspartic acid, and glycine, (approximately 37.4, 24.5, and 23.0 mg/ g of sample, respectively). It also contained high level of lysine (23.5 mg/ g of sample) which is an essential amino acid in human diet. In conclusion, the nutritional quality of the cultured P. binotatus is good hence it is a suitable protein source for human consumption. Keywords: Proximate, Amino acids composition, spotted barb, Puntius binotatus